Petrophysical Evaluation of the Sarvak Formation Based on Well Logs in Dezful Embayment, Zagros Fold Zone, South West of Iran - Jooybari, A.; Rezaie, P. (Engineering, Technology & Applied Science Research, 2017)
Dezful embayment in the south west of Iran is part of Zagros fold zone which despite the small area includes almost all of Iran oil production. Sarvak Formation with middle cretaceous (Albin-Turunin) is the second biggest reservoir of Zagros basin, after the Asmari formation. In this study, with well logging data of two wells, by Geolog software, the petrophysical parameters of Sarvak Formation in the Dezful embayment was studied using the contingent Probabilistic method. Petrophysical parameters such as determination of porosity, water saturation, shale volume and lithology were calculated using this data and common cross plots. Based on this evaluation and utilizing cross plots result, the lithology of Sarvak formation in this zone was determined to be Limestone with traces of dolomite and shale. According to the calculated petrophysical properties of the reservoir, and for more accurate assessment, Sarvak Formation was divided to 6 sections. Findings of this research show that Sarvak Formation includes good reservoir parameters only in half its sections (sections 4, 2 and 6).